2008
DOI: 10.1111/j.1469-8137.2008.02461.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the tomato K+/H+ antiporter LeNHX2 confers salt tolerance by improving potassium compartmentalization

Abstract: Summary Here, the function of the tomato (Solanum lycopersicon) K+/H+ antiporter LeNHX2 was studied using 35S‐driven gene overexpression of a histagged LeNHX2 protein in Arabidopsis thaliana and LeNHX2 gene silencing in tomato. Transgenic A. thaliana plants expressed the histagged LeNHX2 both in shoots and in roots, as assayed by western blotting. Transitory expression of a green fluorescent protein (GFP) tagged protein showed that the antiporter is present in small vesicles. Internal membrane vesicles from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
140
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(152 citation statements)
references
References 46 publications
11
140
0
1
Order By: Relevance
“…Similar findings were obtained by overexpression of the tomato protein NHX2 (Rodríguez-Rosales et al, 2008). The long-standing view is that, owing to the reduced volume of the apoplastic space, the principal if not the only line of defense of plant cells to avert cell injury by extracellular salt accumulation is to rely on the sequestration of salt inside the large central vacuoles.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Similar findings were obtained by overexpression of the tomato protein NHX2 (Rodríguez-Rosales et al, 2008). The long-standing view is that, owing to the reduced volume of the apoplastic space, the principal if not the only line of defense of plant cells to avert cell injury by extracellular salt accumulation is to rely on the sequestration of salt inside the large central vacuoles.…”
Section: Discussionsupporting
confidence: 67%
“…Scattered evidence indicated that vacuolar Na + ,K + /H + antiporter (NHX)-type exchangers could serve this critical function in plant cells (Venema et al, 2002;Rodríguez-Rosales et al, 2008Yoshida et al, 2009;Jiang et al, 2010;Leidi et al, 2010). Studies in transgenic tomato (Solanum lycopersicum) showed that overexpression of the vacuolar At NHX1 or the endosomal Le NHX2 Na + ,K + /H + exchangers led to greater K + accumulation (Rodríguez-Rosales et al, 2008;Leidi et al, 2010). Recently, a reverse genetics approach in Arabidopsis has shown that NHX1 and NHX2 proteins sustain the intravacuolar K + concentration and, in the process, regulate the vacuolar pH and facilitate cell expansion (Bassil et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…Only later, as Na + concentrations increase within plant cells and the apoplast, and the cytosolic and vacuolar pools of K + are eventually depleted, would the contribution of AtNHX1 to salt tolerance gradually decline, and salt-specific maladies appear (Munns, 2002). Greater K + contents in salt-tolerant transgenic plants expressing NHX proteins have also been described by others (Xue et al, 2004;Wu et al, 2005;Zhao et al, 2006;Rodriguez-Rosales et al, 2008). In addition, the enlarged pool of K + in the vacuoles of tomato plants expressing AtNHX1 required the coordinated accumulation of compatible solutes (Table 3).…”
Section: Discussionmentioning
confidence: 81%
“…All plant NHX-type transporters characterized to date can be classified into two groups: class I and class II (Brett et al, 2005;Pardo et al, 2006). Proteins of class I localize to vacuoles and catalyze Na + /H + and K + /H + exchanges in vitro, whereas the endosomal (non-vacuolar) class-II proteins may show a preference for K + over Na + as the substrate (Venema et al, 2002(Venema et al, , 2003Apse et al, 2003;Rodriguez-Rosales et al, 2008). Biochemical studies have established that AtNHX1, a class-I protein, catalyzes both Na + /H + and K + /H + exchange with similar affinity (Venema et al, 2002;Apse et al, 2003;Yamaguchi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…2). Indeed, expression of the plasma membrane Na + / H + antiporter SlSOS1, 8 and the endosomal and vacuolar K + , Na + /H + antiporters LeNHX2 and LeNHX4 [14][15][16] were found transduction pathway. We undertook a preliminary approach to studying the role of SlSOS2 in salinity tolerance by measuring its transcript levels in two tomato species differing in salt tolerance and grown in the presence and absence of NaCl.…”
Section: Involvement Of Slsos2 In Tomato Salt Tolerancementioning
confidence: 99%